If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 2m + -3 Reorder the terms: 15 = -3 + 2m Solving 15 = -3 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 15 + -2m = -3 + 2m + -2m Combine like terms: 2m + -2m = 0 15 + -2m = -3 + 0 15 + -2m = -3 Add '-15' to each side of the equation. 15 + -15 + -2m = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -2m = -3 + -15 -2m = -3 + -15 Combine like terms: -3 + -15 = -18 -2m = -18 Divide each side by '-2'. m = 9 Simplifying m = 9
| 12+x/11=9 | | x(x)+15x=-56 | | 2.2x-2.4=13 | | 3b^2-7b=40 | | m^4+13m^3+22m^2=0 | | x(x)+10x+25=0 | | 3(x-2)+10x=33 | | 12+m/6=15 | | 8y-16+5y=-59 | | s(s)+10s+24=0 | | 7=4x-5 | | 50-2h=44 | | 4x-8=28-x | | -15x=23(4+4)/(-23) | | 4(-7+x)=5x-1/4 | | -15x=23(4+4)/23 | | c/5+8=-5 | | 8/3+2.4 | | 18+9m=288 | | 15x=23(4+4)/23 | | 9x+4=1+2x | | x+7/4=8/5 | | 2.8x-3.3=-8.9 | | 2(9x+7)-8x=2(5x+4)-12 | | -3c-2+7=4c+2-6c | | -8-6x=28 | | 6y+3=5y-9 | | 2(x-1)=4x+1 | | -12+20p=588 | | 4/3x=52 | | n-(0.05xn)=10000 | | 5(y+7)+y=2(y+5)+6 |